Sonates pour piano seul ... op. 26 ... par Louis van Beethoven. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Charles Hagemann; Germany; Rostock, 2022)
Mid-nineteenth century edition of the Piano Sonata no. 13 in A-flat major, op. 26, published in the series "Sonates pour piano seul" as a "nouvelle edition" by Charles Hagemann in Rostock.